Translanguaging como práctica discursiva de brasileiras e brasileiros na Argentina - Da Silva Santana Lopes, Barbara (2019)
With the intention of legitimizing dynamic linguistic practices in which it's possible to observe the fluidity between two or more languages, we propose a view detached from monolingual hegemonic categories in order to enhance effective communication concerning the use of linguistic repertoire of speakers. In our study, we follow the investigations developed by Ofelia Garcia and Ricardo Otheguy (2015) in which they study Brazilians who live in Buenos Aires and Gran Buenos Aires, observing this communicative practice between groups who share the same discursive resources in their construction of meaning. To analyze that, we make use of original material that was collected as part of a Doctorate thesis. In this practice, we can see the emergence of an identity conformed by migrants that constantly negotiate with their own linguistic repertoires in order to optimize their discourse, by which they constitute their self for the other.
No intuito de legitimar práticas linguísticas dinâmicas em que se observa o uso fluido de duas ou mais línguas, propomos um olhar desvinculado das categorias hegemônicas monolíngues para dar lugar a um estudo sobre a comunicação efetiva no que concerne ao uso do repertório linguístico das e dos falantes. Para este trabalho, nos apoiaremos nos estudos desenvolvidos por Ofelia Garcia e Ricardo Otheguy (2015) para estudar o caso de brasileiras e brasileiros que vivem em Buenos Aires e Gran Buenos Aires onde se observa esta prática comunicativa entre grupos que compartilham os mesmos recursos discursivos na construção de significado. Para tal dispomos de um material autêntico, que consideramos relevante, coletado para uma pesquisa de tese de doutorado. Nesta prática vemos o emergir de uma identidade conformada por migrantes em constante negociação com seu repertório linguístico para otimizar seu discurso na constituição do eu pelo outro.
Keywords: Identity; Discourse; Translanguaging; Identidade^lpt; Discurso; Translanguaging